Analisis Minat Masyarakat dalam Perancangan Digitalisasi untuk Menunjang Potensi Pertanian Desa Sukaharja, Kabupaten Bogor, Jawa Barat - Mohamad Damar Purnama; Hilmia Salsabila; Zahara Aini Kesuma; Salsa Nabila Safitri; Nadya Tendra Sikki; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This study aims to analyze the community’s interest in the digitalization design to support the agricultural potential of Sukaharja Village, Bogor Regency. The village has significant agricultural potential but faces marketing challenges due to limited access to broader markets and dependence on middlemen. The research employed qualitative methods through in-depth interviews and questionnaires distributed to 30 farmers managing commodities such as taro, pineapple, and ornamental plants. The findings indicate that while farmers show high enthusiasm for digital solutions like e-commerce, their digital literacy and technological access remain limited. To address these issues, the team developed a digital platform named “Suka Belanja di Harja,” designed to improve product marketing, provide educational content, and empower local farmers. The initiative had a positive impact by increasing farmers’ motivation and awareness about digital marketing. However, ongoing support, infrastructure improvement, and tailored training are necessary to ensure successful digital transformation in rural agriculture.